2018
DOI: 10.1177/0361198118796714
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Flow of Merging Pedestrian Crowds: How Architectural Design Affects Collective Movement Efficiency

Abstract: The need for developing reliable and rigorous models that can replicate and make predictions of pedestrian crowd evacuations has necessitated an understanding of the impact of architecture on individuals’ interactions with their surroundings and the behavioral rules that govern their movements. Due to the challenges of providing such behavioral data from natural evacuations and previous crowd incidents, simulation-based and laboratory-based evacuation experiments have recently been employed as innovative data-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Second, two symmetric exits on the same wall, two exits locate near different corners on the adjacent walls and two opposite exits locate near the corner or in the middle of the parallel walls performed well during urgent evacuations under their respective conditions. Finally, in some particular configurations, an even symmetry is found more efficient than an asymmetric distribution of exits, which is consistent with the results in [59,60].…”
Section: Discussionsupporting
confidence: 91%
“…Second, two symmetric exits on the same wall, two exits locate near different corners on the adjacent walls and two opposite exits locate near the corner or in the middle of the parallel walls performed well during urgent evacuations under their respective conditions. Finally, in some particular configurations, an even symmetry is found more efficient than an asymmetric distribution of exits, which is consistent with the results in [59,60].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, as the top 2 % scholar in the areas of Traffic and Transport Engineering based on the WOS, Majid Sarvi is another core author of an important research group, including the researchers he supervised (Alhawsawi, 2021;Haghani, 2017;Li, 2020;Shahhoseini, 2018). His recent work extended the application of AI approaches in large-scale mixed traffic evacuation and crowd dynamic modelling and simulation.…”
Section: Cooperation Network Analysismentioning
confidence: 99%
“…In the pedestrian field, researchers have spent a lot of time on the influence of asymmetric structure on pedestrian movement, such as space configuration on dynamics of two merging flows, [35] the effect of symmetry exits layout on evaluation efficiency, [36,37] etc. Similarly, it is found that the asymmetric structure of obstacles in the front of the exit affects the overall evacuation efficiency, such as reducing conflicts at the exit, [38] increasing the escape speed (reducing the tangential momentum), [20] and blocking pedestrians moving.…”
Section: Evacuation Time (S)mentioning
confidence: 99%